Comparison of total and salivary cortisol in a low-dose ACTH (Synacthen) test: influence of three-month oral contraceptives administration to healthy women - Šimůnková, K; Stárka, L; Hill, M; Kříž, L; Hampl, R; Vondra, K (Physiological research, 2008)
The objective of this study was to evaluate the influence of low-dose combined oral contraception (COC) on basal and stimulated (1 microg ACTH test) levels of serum and salivary cortisol (F), cortisone and on basal serum cortisol binding globulin (CBG), adrenocorticotropic hormone (ACTH), dehydroepiadrosterone (DHEA) and calculated free cortisol in healthy young women. Three-month administration of COC resulted in 1) significant increase of basal (454.0+/-125.0 to 860.9+/-179.7 nmol/l) and ACTH-stimulated serum cortisol in 30th min (652.3+/-60.5 to 1374.1+/-240.6 nmol/l); 2) no significant change of basal (15.4+/-7.3 to 18.9+/-8.5 nmol/l) and ACTH-stimulated salivary cortisol at the 30th min (32.4+/-8.8 to 32.9+/-9.0 nmol/l); 3) no significant change of basal serum cortisone (38,8+/-7.68 to 45.2+/-24.2 nmol/l) and ACTH-stimulated cortisone at the 30th (34.8+/-10.9 to 47.0+/-35.7 nmol/l); 4) significant increase of basal ACTH (17.2+/-9.0 to 38.2+/-29.4 ng/l), CBG (991.0+/-161.0 to 2332.0+/-428.0 nmol/l), and 5) no significant change of basal DHEA (24.6+/-15.7 to 22.6+/-11.7 micromol/l) and calculated basal value for free cortisol (22.8+/-14.9 to 19.2+/-6.9 nmol/l). In conclusions, higher basal and ACTH-stimulated serum cortisol were found after three-month administration of COC, while basal and stimulated salivary cortisol were not significantly affected. Therefore, salivary cortisol can be used for assessment of adrenal function in women regularly using COC.
Keywords: Carrier Proteins; hydrokortison; adrenokortikotropní hormon; kortison; sliny; Pituitary-Adrenal Function Tests; transportní proteiny; lidé; Adult; dospělí; Saliva; Dehydroepiandrosterone; nemoci nadledvin; Reference Values; Female; ženské pohlaví; dehydroepiandrosteron; Cortisone; Drug Interactions; referenční hodnoty; Humans; Adrenal Gland Diseases; hypofyzoadrenální funkční testy; kontraceptiva orální; lékové interakce; Contraceptives, Oral; Adrenocorticotropic Hormone; Hydrocortisone